A Dual-Focus Reflector Antenna Concept for Spaceborne SAR Systems with Digital Beamforming - Huber, Sigurd; Younis, Marwan; Krieger, Gerhard; Moreira, Alberto (IEEE Transactions on Antennas and Propagation, 2013)
Future spaceborne synthetic aperture radar (SAR) missions shall benefit from digital beamforming (DBF) techniques with the goal of generating high-resolution wide-swath imagery. The basic idea is to replace parts of the analog receiver hardware by digital components, increasing the flexibility of such systems. The limited transmit power rises the need of large antennas capable of electronically steering the antenna beam over a large angular domain. An innovative concept is the usage of large unfoldable mesh-reflector antennas in combination with digital feed arrays. An inherent problem of such systems is, that every feed element illuminates, after reflection from the main reflector, an essentially non-overlapping angular domain in the far field. In case of an element failure the radar system would be ′blind′ in the specific direction. To circumvent costly redundant receiver hardware a new approach to increase the reliability of such systems has been studied. The approach is based on a so called defocused reflector which grants visibility of the complete angular domain under failure conditions. This article presents the electromagnetic considerations leading to the defocused reflector concept. The performance of the defocused reflector system is evaluated in comparison to a conventional parabolic reflector system, utilizing digital beamforming techniques.
DLR Import::2019-04-02